Smart home service perception degradation positioning scheme based on the network resource tree and information entropy - Meng MING; Yu SHI; Runhan ZHENG; Yunxi FENG (Dianxin kexue)
With the accelerating pace of development of the science and technology and informatization, the smart home market is developing rapidly.It brings great convenience to people’s lives, also brings new operation and maintenance tests to operators.A scheme based on big data and AI algorithm, combined with the network resource tree and information entropy was proposed for perceptual real-time monitoring of smart home services, delimiting, segmenting and locating perceptual degradation class faults, aiming to solve the problems of more end-to-end links of smart home services and difficulties in manual location of group faults and single user faults.